2018
DOI: 10.1093/ptep/pty033
|View full text |Cite
|
Sign up to set email alerts
|

Enhancements in F-theory models on moduli spaces of K3 surfaces with ADE rank 17

Abstract: We study the moduli of elliptic K3 surfaces with a section with the ADE rank 17. While the Picard number of a generic K3 surface in such moduli space is 19, the Picard number is enhanced to 20 at special points in the moduli. K3 surfaces become attractive K3 surfaces at these points. Either of the following two situations occurs at such special points: i) the Mordell-Weil rank of an elliptic K3 surface is enhanced, or ii) the gauge symmetry is enhanced. The first case i) is related to the appearance of a U (1)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…3 See, e.g. [48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76] for discussions of F-theory on elliptic fibrations with a global section. 4 When F-theory is compactified on a Calabi-Yau genus-one fibration Y , the discrete gauge group arising in this compactification is identified with the discrete part of the "Tate-Shafarevich group," X(J(Y )), of the Jacobian, J(Y ) [47,19].…”
Section: Introductionmentioning
confidence: 99%
“…3 See, e.g. [48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76] for discussions of F-theory on elliptic fibrations with a global section. 4 When F-theory is compactified on a Calabi-Yau genus-one fibration Y , the discrete gauge group arising in this compactification is identified with the discrete part of the "Tate-Shafarevich group," X(J(Y )), of the Jacobian, J(Y ) [47,19].…”
Section: Introductionmentioning
confidence: 99%
“…This formulation enables the axiodilaton to admit an SL 2 (Z) monodromy. F-theory compactifications on elliptic fibrations with a global section have previously been analyzed [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29]. Furthermore, the physical interpretation of F-theory compactification on a genus-one fibration without a section was recently discussed in [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The rank of the group formed by the set of the global sections of the compactification space -or the "Mordell-Weil group"-yields the number of U (1) factors forming in F-theory on the space [3]. The rank 1 Recent studies of F-theory models on elliptic fibrations that admit a global section can be found, for example, in [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34].…”
Section: Introductionmentioning
confidence: 99%